Storage and retrieval of quantum information with a hybrid optomechanics-spin system. (4th July 2016) - Feng, Zhi-Bo; Zhang, Jian-Qi; Yang, Wan-Li; Feng, Mang
Abstract: We explore an efficient scheme for transferring the quantum state between an optomechanical cavity and an electron spin of diamond nitrogen-vacancy center. Assisted by a mechanical resonator, quantum information can be controllably stored (retrieved) into (from) the electron spin by adjusting the external field-induced detuning or coupling. Our scheme connects effectively the cavity photon and the electron spin and transfers quantum states between two regimes with large frequency difference. The experimental feasibility of our protocol is justified with accessible laboratory parameters.